Mapping the lack of public initiative against female genital mutilation in Denmark - Gro Møller Christoffersen; Peter James Bruhn; Rosanna de Neergaard; Susanne Engel; Vibeke Naeser (BMC, 2018)
Abstract Background Female genital mutilation (FGM) is a harmful practice prevalent in 35 countries, mainly in Africa, as well as in some Middle Eastern countries and a few Asian countries. FGM comprises all procedures that involve partial or complete resection of, or other injury to, external female genitalia for non-medical reasons. The practice of FGM has spread to Western countries due to migration. The European Institute for Gender Equality recommend that FGM be combatted by nationally coordinated efforts through implementation of national action plans, guidelines for professionals as well as comprehensive research in the field. FGM was outlawed in Denmark 2003, but no national actions plan has been implemented. Instead, the task of combatting FGM is currently under the responsibility of local governments in the form of the 98 municipalities. The aim of this study is to investigate the Danish municipalities' efforts to prevent FGM on the local level, and whether these initiatives are in accordance with international recommendations and standards. Methods All 98 Danish municipalities were invited to respond to a questionnaire regarding FGM in their respective municipalities. The inclusion process and questionnaire was designed after a pilot study, which included 29 municipalities. The questionnaire consisted of four overall areas of focus: "action plan", "registration", "information material" and "preventive initiatives". Demographic data were gathered from the 2017 census by Statistics Denmark. Risk countries were defined as countries with a tradition for FGM, identified from the 2016 UNICEF definition. Results A total of 67 municipalities participated in the study. At the time of census, 1.8% of the Danish population was immigrants with origins in risk countries. A total of 10.4% of the responding municipalities indicated to have implemented a specific action plan against FGM. A total of 7,5% had implemented specific preventive initiatives against FGM. Registration of reported FGM cases were indicated to be performed in 73.1% of the responding municipalities; however, only 17.9% stated to perform registration of FGM specifically as such, and not as general child abuse. Conclusions Our study shows that the current situation of FGM registration and prevention being under local administrative responsibility in the 98 Danish municipalities has led to a severe lack of coordinated public initiative against FGM.